Local induction of the alc gene switch in transgenic tobacco plants by acetaldehyde - Sonnewald, Uwe; et al. (Plant and Cell Physiology, 2004)
The alc promoter system, derived from the filamentous fungi Aspergillus nidulans, allows chemically regulated gene expression in plants and thereby the study of gene function as well as metabolic and developmental processes. In addition to ethanol, this system can be activated by acetaldehyde, described as the physiological inducer in A. nidulans. Here, we show that in contrast to ethanol, acetaldehyde allows tissue-specific activation of the alc promoter in transgenic tobacco plants. Soil drenching with aqueous acetaldehyde solutions at a concentration of 0.05% (v/v) resulted in the rapid and temporary induction of the alc gene expression system exclusively in roots. In addition, the split root system allows activation to be restricted to the treated part of the root. The temporary activation of the alc system by soil drenching with acetaldehyde could be prolonged over several weeks by subsequent applications at intervals of 7 d. This effect was demonstrated for the root-specific induction of a yeast-derived apoplast-located invertase under the control of the alcohol-inducible promoter system. In leaves, which exhibit a lower responsiveness to acetaldehyde than roots, the alc system was induced in the directly treated tissue only. Thus, acetaldehyde can be used as a local inducer of the alc gene expression system in tobacco plants.
Keywords: acetaldehyde; alc system; apoplastic invertase; chemically inducible gene expression; nicotiana tabacum; root-specific induction